2012
DOI: 10.2147/copd.s38119
|View full text |Cite
|
Sign up to set email alerts
|

Clinical COPD Questionnaire score (CCQ) and mortality

Abstract: IntroductionThe Clinical COPD Questionnaire (CCQ) measures health status and can be used to assess health-related quality of life (HRQL). We investigated whether CCQ is also associated with mortality.MethodsSome 1111 Swedish primary and secondary care chronic obstructive pulmonary disease (COPD) patients were randomly selected. Information from questionnaires and medical record review were obtained in 970 patients. The Swedish Board of Health and Welfare provided mortality data. Cox regression estimated surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 24 publications
2
37
1
Order By: Relevance
“…In addition, the CCQ proved to correlate with the St George’s Respiratory Questionnaire, generic HRQL instrument SF-36 ® ,29 and CRQ-SR 28. Interesting data from a study updated in 2012 showed that the final low CCQ score was associated with low HRQoL and high mortality risk in COPD patients 46. The CCQ from this study, with its brevity and simplicity, makes it a translatable Thai version, and was suitable for routine use in this study.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the CCQ proved to correlate with the St George’s Respiratory Questionnaire, generic HRQL instrument SF-36 ® ,29 and CRQ-SR 28. Interesting data from a study updated in 2012 showed that the final low CCQ score was associated with low HRQoL and high mortality risk in COPD patients 46. The CCQ from this study, with its brevity and simplicity, makes it a translatable Thai version, and was suitable for routine use in this study.…”
Section: Discussionmentioning
confidence: 98%
“…In regard to this aim, the MARKO questionnaire showed a higher sensitivity for early symptoms of future possible COPD than SGRQ or CAT, with high convergent validity correlation with these already validated COPD health status questionnaires. This high convergent validity correlation is also important because it shows specificity for respiratory disorders and could probably mean that it could be associated with already known features of CAT and SGRQ, showing association with many facets of COPD, like underlying inflammation, airway limitation, breathlessness, progression of disease, morbidity, and mortality (11-15). On the other hand, at least for the 18-item version, the results were not influenced by common comorbidities and concomitant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the self-administered Clinical COPD Questionnaire (CCQ) is available to measure clinical control in patients with COPD. 34 Another severity index available for use is the Body-Mass Index, Degree of Airflow Obstruction and Dyspnea, and Exercise Capacity (BODE) Index (Table 2), which has been found more reliable as a predictor of patient hospitalization and survival than consideration of FEV 1 measure alone. 35,36 Recognizing that worsening airflow limitation in itself is not the most reliable means of assessing disease severity, a major revision was introduced in the updated GOLD guidelines, recommending use of a novel Combined COPD Assessment tool ( Figure 2), which uses an MMRC grade $ 2 or a CAT score $ 10 as an indication of severe symptom burden.…”
Section: Assessing Severity Of Symptomsmentioning
confidence: 99%